Object Design Style Guide (Audiobook) - Noback, Matthias (Manning Publications, 2019)
Offers both guidelines and guidance on how to achieve a clear, consistent tone across a larger team. From the Foreword by Ross Tuck Objects are the central concept of languages like Java, Python, C#. Applying best practices for object design means that your code will be easy to read, write, and maintain. Object Design Style Guide captures dozens of techniques for creating pro-quality OO code that can stand the test of time. Examples are in an instantly familiar pseudocode, teaching techniques you can apply to any OO language, from C++ to PHP. Object Design Style Guide presents dozens of professional techniques for writing OO code. In it, veteran developer Matthias Noback lays out design rules for constructing objects, defining methods, changing and exposing state, and much more. All examples use instantly familiar pseudocode, so you can follow along in the language you prefer. You'll go case by case as you explore important scenarios and challenges for object design and then walk through a simple web application that demonstrates how different types of objects can work together effectively. about the technology Well-written OO code is a pleasure to read, modify, and debug. Elevate your coding style by mastering the universal best practices for object design presented in this book. These clearly presented rules, which apply to any OO language, maximize the clarity and durability of your codebase and increase productivity for you and your team. about the book Object Design Style Guide presents dozens of professional techniques for writing OO code. In it, veteran developer Matthias Noback lays out design rules for constructing objects, defining methods, changing and exposing state, and much more. All examples use instantly familiar pseudocode, so you can follow along in the language you prefer. You'll go case by case as you explore important scenarios and challenges for object design and then walk through a simple web application that demonstrates how different types of objects can work together effectively. what's inside Universal design rules for a wide range of objects Best practices for testing objects A catalog of common object types Exercises for each chapter to test your object design skills about the audience For developers familiar with an object-oriented language and basic application architecture. about the author Matthias Noback is a professional web developer with nearly two decades of experience. He runs his own web deve...